Tobacco experimentation, prevalence and associated factors among brazilian school children: hierarchical model (Research, Society and Development, 2022)
Objective: to analyze the prevalence of tobacco experimentation in Brazilian schoolchildren and its association with demographic, socioeconomic, mental and behavioral health variables. Methods: A cross-sectional study with 102,072 Brazilian students using data from the National School Health Survey carried out in 2015, among students who attended the 9th year of Elementary School. The hierarchical block model was used to analyze the association between the factors and tobacco experimentation. Results: a greater number of risk factors was evidenced in block IV, composed of behavior and life habits, which showed to be associated with tobacco experimentation (p